Functional assessment of daily living activities following surgical management of young-burgess lateral compression type-II pelvic fractures with combined anterior and posterior internal fixation - Eskander, Shah Md. Faisal; Orchi, Proma; Mahmud, Khaled; Saikat, Nurul Mahmud; Rahman, M. Ashiqur (International Journal of Research in Orthopaedics, 2023)
Background: Fractures of the ischiopubic bones, S-I joint, and sacrum are among the most common bony injuries. Various procedures are available for managing this condition. Biomechanically, internal fixation of both the posterior and anterior lesions can offer complete stability to the pelvic ring. This study aimed to assess the functional assessment of daily living activities following surgical management of young-burgess lateral compression type-II pelvic fractures with combined anterior and posterior internal fixation. Methods: This descriptive observational study was conducted at the Department of Orthopedics & Traumatology, Dhaka Medical College & Hospital, Dhaka, Bangladesh from July 2016 to June 2018. A total of 44 patients with pelvic injuries admitted to the respective department were purposively enrolled as the study population. Data analysis was performed using the MS Office tools. Results: Most patients (68.18%) continued their jobs with reduced performance, while 22.72% maintained both job and performance levels. Regarding functional assessment, 54.54% could sit pain-free, with only 13.63% experiencing discomfort. None reported painful sexual intercourse. Mobility-wise, no one was bedridden or could only walk a few meters, and 0% needed walking sticks. Additionally, 18.81% could walk for one hour with a stick, while 63.63% had a normal walking distance for their age. No limitations in walking time or distance were observed in 63.63% of cases. Conclusions: This study concludes that stabilization of LC type-II pelvic ring fractures by anterior, combined, or posterior reconstruction plate provides a good result concerning daily living activities.